Analysis of Melamine Using Electronic Nose, Gas Chromatography-Time of Flight - Mass Spectrometry and High Performance Liquid Chromatography - Rohman., Abdul; Che Man, Yaakob B.; Hafidz, R. M. (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
An electronic nose (E-Nose) has been used as rapid analytical technique for melamine detection in food samples. The parameter used is melamine retention index (MRI) in E-Nose chromatogram. The value of MRI was also confirmed using two dimensional gas chromatography-time of flight-mass spectrometry (GCxGC-TOF-MS). The value of MRI using E-Nose and GCxGC-TOF-MS was nearly close i.e 1486 and 1540 respectively. HPLC has been used for quantitative analysis of melamine in some milk products suspected to contain melamine using column Nova-Pak® C18;(150 x 3.9 mm i.d; 4 µm) at 30°C. The mobile phase was 5 mmol L−1 NaH2PO4 delivered isocratically at flow rate of 1 mLmin-1 . Melamine was linear at concentration range of 0.0625 – 50.0 µg/ml with coefficient of determination (R2 ) of 0.999.